2020
DOI: 10.3390/w12071940
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Recharge-Storage-Runoff Process of the Yangtze River Source Region under Climate Change

Abstract: Storage and runoff are the two fundamental surface hydrological variables of a catchment. Research studies have been focused on the storage-runoff (S-R) hysteretic relationship of a catchment and its explanation very recently, thanks to satellite gravimetry. However, a complete analysis of a hydrological process starting from recharge to runoff has not been investigated. The S-R hysteretic relationship of Yangtze River Source Region (YRSR) situated in the northeast Tibetan Plateau is also unexplored. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Previous research studies have found that runoff lagged the upstream GPM-TRMM precipitation (Zhang et al, 2007;Du et al, 2020) and GRACE water storage (Riegger and Tourian, 2014) by a month or more. Thus, the time lag between the upstream GPM-TRMM precipitation (GRACE water storage) and the runoff must be determined before further calculation.…”
Section: Linear Regression Modelmentioning
confidence: 94%
“…Previous research studies have found that runoff lagged the upstream GPM-TRMM precipitation (Zhang et al, 2007;Du et al, 2020) and GRACE water storage (Riegger and Tourian, 2014) by a month or more. Thus, the time lag between the upstream GPM-TRMM precipitation (GRACE water storage) and the runoff must be determined before further calculation.…”
Section: Linear Regression Modelmentioning
confidence: 94%
“…Owing to the hysteretic process between the remotely-sensed climatic variables (i.e., TRMM precipitation and GRACE land water storage) and the runoff within a river basin, there exists a time lag between the remotely-sensed climatic variables and the runoff time series, particularly for the Mekong Basin across different climate zones. Previous studies have shown that the runoff lagged behind the upstream TRMM precipitation [61,62] and GRACE land water storage [28] by a month or more, which is controlled by climate, geomorphology, and hydrogeology [29]. Thus, the time lag between the in situ runoff and the upstream spatially-averaged TRMM precipitation (or GRACE land water storage) has to be determined before the linear regression.…”
Section: Time Lag Determination Linear Regression Model and Nn-based ...mentioning
confidence: 99%
“…However, hysteresis has been known for a long time in soil physics and soil hydrology and associated with water flowing through porous media [68,92]. Furthermore, hysteresis is found in surface hydrology, where sediment transport studies in streams show that sediment yields may depict such behaviour, as well as ionic species dissolved or adsorbed to the soiled phase [64,93,94].…”
Section: Soil Water Recharge and Depletionmentioning
confidence: 99%
“…Most studies referenced above used hydrological modelling based on water balance approaches applied at large spatial scales and a common conclusion was that the joint assimilation of soil moisture and total water storage remote data improves model performance [60][61][62]. Furthermore, the validation of radar products is commonly performed with meteorological data matrices that are obtained from satellite data, such as NOOA or Meteosat (e.g., [18,[60][61][62][63][64][65]). Table 1 is presented to condense the relevant literature on the topic.…”
Section: Introductionmentioning
confidence: 99%